Impact of Augmented Video-Verbal Encouragement Feedback on Motivation and Technical Performance in Novice Cricket Athletes - Hasan Basri; Taufik Rihatno; Abdul Sukur; Samsudin Samsudin; Giri Prayogo; Firmansyah Dlis; Akhmad Dimyati; Ahmet Kurtoğlu; Amayra Tannoubi; Dan Iulian Alexe; Maciej Śliż; Zihan Novita Sari; et al. (Jan Długosz University in Częstochowa, 2024)
This study aims to investigate the effect of using augmented video feedback (AVF)-verbal encouragement feedback (VEF) on the motivation and technical performance of novice cricket athletes. A true experimental method with a random control trial (RCT) design for 11 weeks was adopted in this study. 60 beginner male cricket athletes from the State University of Jakarta (Indonesia) were involved asparticipants in this research. They were divided into two groups, experimental (AVF-VEF, n = 30, 19.2 ± 1.06 years) and control (CG, n = 30,18.9 ± 1.17 years) one. Sport motivation scale-II (SMS-II) and batting, bowling, and fielding were chosen as instruments. Two-way repeated measures ANOVA conducted on motivation and technical performance tests showed a significant effect of Time (all, p <0.05), a significanteffect of Group (all, p <0.05) and a significant interaction for Group*Time (all, p <0.05). Student's paired t-test carried out on two groupsseparately showed that AVF-VEF could significantly increase the mean score of motivation and technical performance more than the CG programme. This research highlights the importance of applying AVF-VEF as a training tool to improve motivation and technical performancein entry-level cricket athletes.